Implementasi Kurikulum Merdeka (IKM) di Sekolah Dasar dalam Mengembangkan Profil Pelajar Pancasila - Angga; Asep Herry Hernawan; Tita Mulyati (Elementary Teacher Education Program, Majalengka University, 2023)
The application of the Pancasila student profile can strengthen character and competency development, train problem-solving skills, and be responsible and concerned about issues around. This study aims to describe the implementation of the independent curriculum in developing the profile of Pancasila students in elementary schools. The research method used is the study of literature. Data collection with the keywords